Complete dissociation of DOCA-salt hypertension and red cell ion transport alterations - Bin Talib, H K; Kunes, J; Zicha, J (Life sciences, 1992)
Our previous study revealed major ion transport alterations that resulted in a pronounced elevation of red cell Na+ content in DOCA-salt treated homozygous vasopressin-deficient (DI) Brattleboro rats in which only a moderate increase of systolic blood pressure occurred. In contrast, no changes of red cell Na+ content were observed in heterozygous vasopressin-secreting (non-DI) Brattleboro rats with a severe DOCA-salt hypertension. Using a chronic supplementation of DI rats with an antidiuretic agonist dDAVP (1-desamino-8-D-arginine vasopressin) we did not demonstrate any significant changes of red cell ion transport in dDAVP-treated DI rats with a fully developed DOCA-salt hypertension. The absence of ion transport alterations seems to be mainly due to dDAVP-induced correction of altered K+ metabolism seen in DOCA-salt treated DI animals. It can be concluded that DOCA-salt hypertension can develop even without red cell ion transport alterations which are usually caused by cell K+ depletion.
Keywords: iontový transport; Animals; draslík; Sodium; Female; Potassium; ženské pohlaví; desmopresin; erytrocyty; Osmolar Concentration; renovaskulární hypertenze; vasopresiny; Vasopressins; krevní tlak; Ion Transport; tělesná hmotnost; osmolární koncentrace; Erythrocytes; sodík; Hypertension, Renovascular; krysa rodu Rattus; Body Weight; Desoxycorticosterone; Deamino Arginine Vasopressin; zvířata; deoxykortikosteron; Blood Pressure; Rats, Brattleboro; Rats; potkani Brattleboro